Medicinal Effects of Agathosma (Buchu) Extracts - Huisamen, Barbara (AOSIS, 2019)
The research results presented in this book span the quest of Cape Kingdom Nutraceuticals, Prof. Patrick Bouic and Prof. Barbara Huisamen to scientifically validate the health promoting properties of an aqueous extract of the plant Agathosma. To accomplish this, they made use of both in vitro and in vivo models to understand and underscore the anecdotal information of the benefits of this product. Cell based studies highlighted anti-inflammatory and anti-diabetic effects while animal-based studies were utilized to confirm the anti-diabetic effects whilst further elaborating on anti-obesity properties. In addition, technology aimed at small animals were used to follow blood pressure to demonstrate anti-hypertensive effects while ex vivo perfused hearts were studied to show that this extract also protected the heart against an ischaemic incident. In view of the current pandemic of obesity and non-communicable diseases, the research results presented in this book will be of special interest to the scientific community and health practitioners interested in cardiometabolic diseases and nutraceuticals as an alternative treatment option. In view of the failure of many pharmaceuticals to curb non-communicable diseases, these results are deemed of high importance